2010
DOI: 10.3109/15622975.2010.507785
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric disorders in individuals with high-functioning autism and Asperger's disorder: Similarities and differences

Abstract: From a clinical perspective, it could be concluded that both disorders involve a high risk for developing psychiatric disorders, with AS patients at greater risk for depression. From a nosological perspective, the substantial similarities in terms of psychiatric comorbidity may support the idea that both disorders are on the same spectrum and differs in some aspects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
56
2
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(67 citation statements)
references
References 25 publications
5
56
2
4
Order By: Relevance
“…Depression can often arise with an increase of withdrawal and aggressive behaviours: these symptoms may present more clearly in patients with HFA/AS, rather than in low-functioning autism (LFA), which could primarily presenting withdrawal and aggression. From other studies has been reported a very broad range of prevalence of mood disorders, from 6% up to 70% [4,5,[15][16][17][18][19]. This variability could depend to the fact that some authors examined only AS patients, other ones considered depressive symptoms rather then a diagnosis of major depression.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Depression can often arise with an increase of withdrawal and aggressive behaviours: these symptoms may present more clearly in patients with HFA/AS, rather than in low-functioning autism (LFA), which could primarily presenting withdrawal and aggression. From other studies has been reported a very broad range of prevalence of mood disorders, from 6% up to 70% [4,5,[15][16][17][18][19]. This variability could depend to the fact that some authors examined only AS patients, other ones considered depressive symptoms rather then a diagnosis of major depression.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, two patients had oppositional defiant disorder (5.6%), compared to 1% in the study of Simonoff, to 16% according to Mattila et al [5], up to 30% according Mukkades et al [4]. Must be considered that aggression, often found in ODD, is common in ASD patients, most of all in LFA; moreover, could be the epiphenomenon of other types of comorbidity, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations